The complete fairy tales - Grimm, Jacob, 1785-1863; Zipes, Jack, 1937-; Crane, Walter, 1845-1915 (London : Vintage, 2007)
A woman who serves her stepson up in a stew, a man marries a snake, and a princess sleeps with a frog. Violent, funny, disturbing, wise and sometimes beautiful, these stories have intrigued children, adults, scholars, psychologists and artists for centuries and are collected together in this single volume.
Translated from the German.
Includes bibliographical references and index.
Keywords: Fairy tales -- Germany